2009
DOI: 10.1111/j.1460-9568.2009.06805.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological evidence for attentional guidance by the contents of working memory

Abstract: The deployment of visual attention can be strongly modulated by stimuli matching the contents of working memory (WM), even when WM contents are detrimental to performance and salient bottom-up cues define the critical target [D. Soto et al. (2006)Vision Research, 46, 1010-1018]. Here we investigated the electrophysiological correlates of this early guidance of attention by WM in humans. Observers were presented with a prime to either identify or hold in memory. Subsequently, they had to search for a target lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
93
6
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(113 citation statements)
references
References 45 publications
12
93
6
2
Order By: Relevance
“…(C) Visual working memory capacity task (see Luck & Vogel, 1997); participants reported whether the memory probe color was same or different from the item at that location in the sample array. (D) Automated operation span task (Unsworth et al, 2005); participants alternated between remembering letters and solving arithmetic problems differential modulation of the N2pc event-related potential component) from these two types of paradigms (Carlisle & Woodman, 2011b, 2013Kumar, Soto, & Humphreys, 2009). Taken together, these findings challenge the assumption in this field that both types of paradigms probe the same underlying processes of how WM contents guide attention.…”
Section: Introductioncontrasting
confidence: 49%
“…(C) Visual working memory capacity task (see Luck & Vogel, 1997); participants reported whether the memory probe color was same or different from the item at that location in the sample array. (D) Automated operation span task (Unsworth et al, 2005); participants alternated between remembering letters and solving arithmetic problems differential modulation of the N2pc event-related potential component) from these two types of paradigms (Carlisle & Woodman, 2011b, 2013Kumar, Soto, & Humphreys, 2009). Taken together, these findings challenge the assumption in this field that both types of paradigms probe the same underlying processes of how WM contents guide attention.…”
Section: Introductioncontrasting
confidence: 49%
“…We discuss only the ERP results that are relevant to our hypothesis, thus omitting our findings regarding validity as well as validity and task interactions, which have been previously been discussed (Kumar et al 2009). Our main finding was the interaction between task and cue, which was present in all three components of interest: the P3, the LPP and the SPCN.…”
Section: Discussionmentioning
confidence: 94%
“…This paradigm is useful because it enables us to assess whether the longlatency ERPs modulated by food are affected by factors such as memory or merely attending to the picture. The WM-based guidance paradigm has been examined once before in an ERP study, but there was no examination of different cue types (Kumar et al 2009). In the present study, for the first time, we directly compare food and nonfood cues and examine the modulatory effects of food on late-acting ERP components to provide us insight into the electrophysiological correlates of food-related memory coding and attention.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent work has shown that the item held in WM can even influence search for a "pop-out" target (Soto, Humphreys, & Heinke, 2006b), suggesting that there is modulation of early stages of visual processing from information held in WM. Consistent with this Kumar, Soto, and Humphreys (2009) report effects on the N2pc component of the event-related electroencephalography (EEG) response reflecting the fast initial orienting of spatial attention to the side of the display containing a stimulus matching the WM content. Soto, Humphreys, and Heinke (2006a) examined whether this WM effect was apparent in patients with unilateral lesions of the frontal lobe based around the middle frontal gyrus.…”
mentioning
confidence: 58%
“…was focused to process another stimulus (Experiment 3), and when the contingency relationship between the cue and target reduced (Experiment 4). We suggest that these are all conditions in which control was expected "externally" triggered through changes in the tasks or in stimulusresponse contingencies (see Kumar et al, 2009).…”
Section: Limits Of Top-down Controlmentioning
confidence: 97%